Recent progress towards the transition-metal-catalyzed Nazarov cyclization of alkynes via metal carbenes. Issue 24 (1st June 2021) - Ru, Guang-Xin; Zhang, Ting-Ting; Zhang, Meng; Jiang, Xiao-Lei; Wan, Zheng-Kai; Zhu, Xiu-Hong; Shen, Wen-Bo; Gao, Guang-Qin
Abstract : This review is to highlight the recent progresses in the transition-metal-catalyzed Nazarov cyclization of alkynes via metal carbenes, such as α-oxo metal carbene, α-imino metal carbene, α-phenyl metal carbene and α-cyclopropyl metal carbene. Abstract : In recent years, transition-metal-catalyzed tandem cyclization reactions of alkynes, especially those involving a metal carbene intermediate, have received worthwhile interest, as this type of reaction does not require the use of risky and potentially explosive diazo compounds as starting materials for carbene generation. A significant and general strategy for the stereospecific synthesis of 5-membered cycles is Nazarov cyclization based on the 4π-conrotatory electrocyclization of a conjugated pentadienyl cation to afford a cyclopentenyl cation. In this review, we introduce an overview of recent advances in the transition-metal-catalyzed Nazarov cyclization of alkynes via a metal carbene intermediate, and categorize these reactions according to the structure of the metal carbene. Our aim is to accelerate advancements in this enchanting area of research.